Involvement of Interleukin-10 in the Anti-Inflammatory Effect of Sanyinjiao (SP6) Acupuncture in a Mouse Model of Peritonitis. (5th June 2011) - da Silva, Morgana Duarte; Guginski, Giselle; de Paula Werner, Maria Fernanda; Baggio, Cristiane Hatsuko; Marcon, Rodrigo; Santos, Adair Roberto Soares
Abstract : In this study, we determined the anti-inflammatory effect of manual acupuncture at the Sanyinjiao or Spleen 6 (SP6) point on carrageenan-induced peritonitis in mice and investigated mechanisms that may underlie this effect. In the first set of experiments, male Swiss mice were allocated into five groups: the control (sterile saline), dexamethasone (DEXA), invasive sham-acupuncture (non-acupoint), SP6 acupuncture and carrageenan-treated groups. Ten minutes after needle retention or 30 min after DEXA treatment, mice received an intraperitoneal injection of carrageenan (750 μg/mouse). After 4 h, total leukocyte and differential cell counts (neutrophils and mononuclear), myeloperoxidase (MPO) activity, vascular permeability and cytokine levels were evaluated. In another set of experiments, adrenalectomized (ADX) mice were used to study the involvement of the adrenal gland on the therapeutic effects of acupuncture. Mice were allocated into two groups: the ADX and sham-operated animals (Sham ADX) that were subdivided into four subgroups each: the control (sterile saline), DEXA, SP6 acupuncture and carrageenan-treated groups. The SP6 and DEXA treatments inhibited the inflammatory cell infiltration, vascular permeability and MPO activity in carrageenan-injected mice. In addition, the SP6 treatment also increased interleukin (IL)-10 levels. In contrast, when the animals were adrenalectomized, the SP6 treatment failed to reduce total leukocyte and the plasma extravasation. In conclusion, this study clearly demonstrates the anti-inflammatory effect of SP6 acupuncture in a model of carrageenan-induced peritonitis. Our results demonstrated that SP6 acupuncture depends of the adrenal glands and increased IL-10 levels to produce its anti-inflammatory action.